The Immoralist and the Rhetoric of First-Person Narration - John T. Booker (Studies in 20th & 21st Century Literature, 1977)
Gide's The Immoralist, a short first-person novel written at the beginning of the century, has long been seen as an early example of the unreliable narrator. More recently, critical attention has focused on the tensions set up in the work between the carefully drawn formal structure of the narrative and the claim of Michel, the narrator, to tell his story in a direct and simple manner. Of more general interest, however, is the way Michel's narration provides insight into important developments that have taken place in the first-person novel itself in the twentieth century. Cast initially in a very traditional mold, Michel's story breaks down progressively as it moves from events of a more distant past to those much closer in time to his moment of narration. This breakdown of Michel's narrative seems to presage the movement in the first- person novel in France away from the relation of a story as traditionally conceived and towards the increasing importance accorded the present of narration itself. In that sense, The Immoralist is a key, pivotal work in the long line of short first-person works of fiction in France.
Keywords: Andre Gide; The Immoralist; L' immoraliste; first-person; narration